Problems of applying and realization of preventive measures in the form of detention concerning persons, suspected and accused in the commission of the act of terrorism and crimes of extremist nature - Akimzhanov, Talgat; Amandykova, Saule; Tleukhan, Ramazan; Daurembekov, Yerlan; Aykumbekov, Nurlan (Opción, 2019)
The main content of the article focuses on the substantive aspects of criminal offences of terrorist and extremist right. Special attention is paid to the application of preventive measures related to isolation from society as for persons who have committed crimes of this category. According to the authors opinion, the implementation of the position will enhance the effectiveness of measures of criminal-procedural control over the behavior of persons in the target group that will create the necessary legal safeguards to meet the challenges of criminal justice in the investigation and trial of criminal cases in this category.